2013
DOI: 10.1021/es400642e
|View full text |Cite
|
Sign up to set email alerts
|

Century-Long Source Apportionment of PAHs in Athabasca Oil Sands Region Lakes Using Diagnostic Ratios and Compound-Specific Carbon Isotope Signatures

Abstract: Evaluating the impact that airborne contamination associated with Athabasca oil sands (AOS) mining operations has on the surrounding boreal forest ecosystem requires a rigorous approach to source discrimination. This study presents a century-long historical record of source apportionment of polycyclic aromatic hydrocarbons (PAHs) in dated sediments from two headwater lakes located approximately 40 and 55 km east from the main area of open pit mining activities. Concentrations of the 16 Environmental Protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 69 publications
7
82
1
Order By: Relevance
“…There was no indication of increased toxicity to Daphnia in the fossil record (at least to date), likely due to the greater influence of recent climate change on lake primary production of algae (the food resource of Daphnia). Jautzy et al (2013) reported similar conclusions on the extent and source of PAH contamination.…”
Section: Polycyclic Aromatic Compoundssupporting
confidence: 63%
“…There was no indication of increased toxicity to Daphnia in the fossil record (at least to date), likely due to the greater influence of recent climate change on lake primary production of algae (the food resource of Daphnia). Jautzy et al (2013) reported similar conclusions on the extent and source of PAH contamination.…”
Section: Polycyclic Aromatic Compoundssupporting
confidence: 63%
“…Sediment ΣPAH 13 concentrations reached 14 μg/g dw in Detroit River, but ranged from 0.25 to 2.0 μg/g in other parts of the Huron-Erie Corridor (Szalinska et al, 2011). In two headwater lakes of the Athabasca Oil Sands Region, Canada, ΣPAH 16 concentrations ranged from 100 to 320 ng/g dw throughout the sediment cores (Jautzy et al, 2013). ΣPAH 15 concentrations in Lake Taihu sediments in highly populated eastern China were 209 to 1003 ng/g dw (Zhang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Some source apportionment and forensic studies have been carried out on sediment and soil contamination and usually target individual congeners. 33,38,41 However, no studies have measured all three classes of PACs in air across a regional scale as in this current study, which provides an opportunity to explore class-based ratios.…”
Section: Environmental Science and Technologymentioning
confidence: 97%